Three-dimensional thermal buckling analysis of functionally graded material structures using a modified FSDT-based solid-shell element. (15th December 2021) - Hajlaoui, A.; Chebbi, E.; Dammak, F.
Abstract: - In the current paper, an attempt is made to analyze the thermal buckling behavior of functionally graded (FG) shell structures by using a modified first-order enhanced solid-shell element formulation. The material properties of functionally graded shell are presumed to vary continuously in the thickness direction according to a simple power law distribution. Temperature-independent (TID) and temperature-dependent (TD) material properties are both considered. The modified theory takes into account the shear strains through the FGM shell thickness with a parabolic shape function imposed in the compatible strain part, and it verifies the zero shear stresses condition at the top and bottom surfaces of shell. To subdue locking problems, the assumed natural strain (ANS) method and the enhanced assumed strain (EAS) method with a minimal number of internal parameters are employed. Numerical results of the present research are compared and validated with the existing studies on the thermal buckling of FGM shells. Both uniform and nonuniform temperature distributions are considered. The effect of different parameters on the thermal buckling temperature of FGM structures is highlighted by solving numerous examples. Highlights: Three-dimensional thermal buckling analysis of functionally graded (FG) shell structures is studied. Different types of thermal loading are considered, and temperature dependency is considered. Modified first-order enhanced solid-shell element is developed. A special representation of the transverse shear strains is imposed in the compatible strain part. The shear correction factors are no longer needed.